SOCIOECONOMIC FACTORS AND SMOKING HABITS IN INDONESIA: ANALYSIS OF INDONESIAN FAMILY LIFE SURVEY (IFLS) 2014/2015 - Hapsari, Widiandini Prita (Jurnal Ekonomi Kesehatan Indonesia, 2022)
This study aims to find out what effects affect individuals to become smokers. So that the influence of socio-economic conditions and smoking habits in Indonesia can be helpful to literacy for policymakers. This study uses secondary data from the Indonesia Family Life Survey 2014/2015 (IFLS-5). The main variables in this study were smoking habits, while socio-economic conditions, social demographics and health conditions as control variables to see other factors that influence smoking habits. Using a logistic regression model, the results of this study indicate that several variables that represent socioeconomic conditions have a positive relationship and several other variables have a negative relationship to smoking habits in Indonesia and some show significant results. In the control variable, all demographic factors have a negative and significant effect on smoking habits. People with heart disease have a negative and significant effect, while people with symptoms of depression and physical activity have a positive and significant effect if health conditions are the control variables. With the results of the analysis above, it ends in a discussion of the Human Development Index (HDI) which can be a solution to the problems caused by cigarette consumption in Indonesia.